POLICY IMPLEMENTATION OF THE LOCAL GOVERNMENT REGARDING THE PROHIBITION OF PROPERTY AND IMMORAL CONDUCT - Budi Heryanto; Emaliawati Emaliawati; Aji Mulyana (JCH (Jurnal Cendekia Hukum), 2021)
Prostitution is an activity of offering sex edgaged to people to be enjoyed in general or voluntarily in order to obtain a reward for that person's sexual satisfaction. However, prostitution activity violates the norms and values of society as seen in prostitution activities in Sukabumi Regency area which often disturbs the community. Therefore the regional government issued Regional Regulation Number 5 of 2015 concerning the Prohibition of Prostitution and Immoral Acts which are the result of public policies which are forms or types of legal provisions that must be implemented in society, but at the level of implementation it is still not optimal. The purpose of this study was to find out how the implementation of the Regional Regulation of Sukabumi Regency in carrying out the rules prohibiting prostitution and immoral acts. The implementation of this local government policy has not regulated well because of many factors that affect its implementation, both from the regulation itself, human resources, inadequate facilities and infrastructure.